A pi biomimetic nanostructure and a preparation method and application thereof
Patent Information
- Application Number
- CN202311834516.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-28
AI Technical Summary
[0003]然而目前传统仿生微纳结构制备工艺如纳米压印、等离子刻蚀、模板法、气相沉积等,往往存在成本高昂、难以大批量生产、无法兼容柔性薄膜基板等缺点,且人工仿生制备的纳米结构表面往往难以达到与生物本身相媲美的性能
[0019]1.本发明结合了激光扫描及热释放胶带,可以直接通过激光扫描,无需光刻步骤,具有操作步骤简单、环境污染小等特点,可适用于大面积生产。
Smart Images

Figure CN117800281B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible electronics fabrication technology, and more specifically, relates to a PI biomimetic nanostructure, its fabrication method, and its application. Background Technology
[0002] Biomimetic micro and nano surfaces often possess unique properties such as adhesion, structural color, light trapping, hydrophobicity, and antibacterial properties. By fabricating corresponding microstructures on the surface of flexible electronic device materials, the surface of the device can be endowed with high-strength properties such as superhydrophobicity, light trapping, antibacterial properties, and adhesion. These properties provide new ideas and methods for improving the performance of flexible electronic devices and solving problems in multiple application scenarios. For example, when applied to photovoltaic products, they can improve photoelectric conversion efficiency; when applied to medical implants, they can achieve sterilization and reduce human infection; and when applied to sensor devices, they can improve their sensitivity and response characteristics.
[0003] However, current traditional biomimetic micro / nanostructure fabrication processes, such as nanoimprinting, plasma etching, template methods, and vapor deposition, often suffer from drawbacks such as high cost, difficulty in mass production, and incompatibility with flexible thin-film substrates. Furthermore, the surfaces of artificially biomimetic nanostructures often fail to achieve performance comparable to that of biological structures. Therefore, it is necessary to find an economical, efficient, mass-producible method for fabricating micro / nanostructures that is compatible with flexible thin-film substrates. Summary of the Invention
[0004] In view of the above-mentioned defects or improvement needs of the existing technology, the present invention provides a PI biomimetic nanostructure, its preparation method and application, which can be manufactured on a large area without the need for biological templates.
[0005] To achieve the above objectives, according to one aspect of the present invention, a method for preparing PI biomimetic nanostructures is provided, the method comprising the following steps:
[0006] (1) A PI film is prepared on a substrate, and an ultraviolet laser is used to scan the PI film after passing through the substrate, so that the interface of the laser scanning area undergoes nanoscale cavitation to achieve a sub-exfoliation state. At this time, nanofiber connections are generated between the interface of the PI film and the glass substrate.
[0007] (2) Apply heat release tape to the PI film and use the external force of the heat release tape to peel the PI film off the glass substrate.
[0008] (3) Heat the heat release tape to complete the heat release of the PI film, thereby obtaining the PI biomimetic nanostructure.
[0009] Furthermore, the thickness of the PI film is 1μm to 20μm.
[0010] Furthermore, the laser center wavelength is 308 nm; the laser energy density is 70 mJ / cm².2 -120mJ / cm 2 The number of repeated irradiations ranges from 10 to 900.
[0011] Furthermore, the number of irradiations was repeated 50 times.
[0012] Furthermore, the heat-release tape is heated at 110°C to complete the heat release process of the PI film.
[0013] Furthermore, the height of the nanopillars on the surface of the PI biomimetic nanostructure is increased by increasing the laser energy density and the number of irradiations.
[0014] Furthermore, the density of the nanopillars can be adjusted by regulating the fixed laser energy density and the number of irradiations.
[0015] Furthermore, the isotropy / anisotropy of the nanopillars can be adjusted by regulating the laser scanning method.
[0016] The present invention also provides a PI biomimetic nanostructure, which is prepared by the PI biomimetic nanostructure preparation method described above.
[0017] The present invention also provides an application of the PI biomimetic nanostructure described above in hydrophobic structures.
[0018] In summary, compared with the prior art, the PI biomimetic nanostructures, their preparation methods, and applications provided by this invention have the following beneficial effects:
[0019] 1. This invention combines laser scanning and heat-release tape, which can be directly scanned by laser without photolithography. It features simple operation, low environmental pollution, and is suitable for large-area production.
[0020] 2. The micro-nano structures prepared by this invention are compatible with flexible substrates and can be used to prepare surface micro-nano structures on flexible films.
[0021] 3. Changes in nanomorphology can be controlled by adjusting laser parameters. For example, the height of nanopillars can be increased by reducing the laser energy density and increasing the number of irradiations. The density of nanopillars can be changed by fixing the energy density and the number of irradiations. The isotropy / anisotropy of nanopillars can be controlled by scanning.
[0022] 4. The prepared nano-surface exhibits excellent hydrophobicity. The hydrophobicity of the PI nanostructure surface was quantitatively demonstrated using a contact angle meter. It was found that the static contact angle of the surface with the PI nanostructure reached 133°, while the static contact angle of the smooth control PI surface was 85.2°. This indicates that the morphology of the nanostructure can change the wettability of the material itself. The measurement results showed that the static contact angle of the dragonfly wing was 133.7°, indicating that the PI biomimetic nanostructure prepared in this invention has a similar level of hydrophobicity to the microstructure of the dragonfly wing surface.
[0023] 5. It has a good light trapping effect. The overall transmittance of the nano-PI film is increased by ~7% compared with the smooth film, and the overall reflectance is reduced by ~7%. Moreover, due to the absorption of ultraviolet light by the PI film, the surface reflectance in the band of about 400nm is only 1.5%. Attached Figure Description
[0024] Figure 1 This is a schematic flowchart of a method for preparing a PI biomimetic nanostructure provided by the present invention;
[0025] Figure 2 (a) and (c), (b) and (d) in the figure are respectively the dragonfly wing and its surface nanomorphology, and the PI nanofilm prepared by the present invention and its surface morphology;
[0026] Figure 3a and Figure 3b These are schematic diagrams showing the interface evolution process and interface state of the biomimetic nanostructure prepared by this invention under laser irradiation.
[0027] Figure 4 (a), (b), (c), (d), and (e) are schematic diagrams of different states of nanoscale cavitation at the interface when laser scanning continuously acts on PI.
[0028] Figure 5 The sub-peeling threshold and peeling threshold under multiple sets of different energy densities were statistically analyzed, and a schematic diagram of the relationship between laser energy density and laser scanning number corresponding to the sub-peeling state of the PI interface was established.
[0029] Figure 6 This is a schematic diagram illustrating the adhesion of the functional interface described in this invention under multiple sets of repeated test results with different laser irradiation times;
[0030] Figure 7 This is a schematic diagram showing the change in the interface transmittance of the functional interface described in this invention under multiple sets of repeated test results with different laser irradiation times.
[0031] Figure 8(a) and (b) in the figure are nanocolumn morphology diagrams under different laser irradiation times for the nanofunctional surface described in this invention;
[0032] Figure 9 (a), (b), (c), and (d) in the figure are statistical graphs showing the changes in the density and height of the nanopillars as a function of APN.
[0033] Figure 10 These are images of nanopillar morphology under different laser energy densities in the laser process described in this invention;
[0034] Figure 11 This is a statistical graph showing the change in the height of the nanopillars as a function of laser energy density;
[0035] Figure 12 (a), (a1), (a2), (b), (b1), and (b2) represent the morphologies of nanopillars under different laser scanning methods; they are set to two scanning methods: unidirectional scanning (scanning direction vertically downward) and vertical cross scanning (scanning directions are horizontal and vertical superimposed);
[0036] Figure 13 (a) and (b) in the figure are the transmission and reflection spectra of the nanostructured PI film of the present invention under different laser irradiation conditions, respectively;
[0037] Figure 14 (a), (b), (c), (d), (e), and (f) are schematic diagrams comparing the hydrophobic properties of the nanostructured PI film and the dragonfly wing described in this invention, respectively.
[0038] Figure 15 This is a schematic diagram of the process for preparing a nano-coating on transparent PI using the laser scanning process described in this invention;
[0039] Figure 16 (a) and (b) in the figure are comparisons of the transmittance and reflectance of dragonfly wings with and without nanostructured PI films at different angles.
[0040] Figure 17 This is a SEM image of the pre-stripping area and its local morphology irradiated by laser scanning at the edge of a PI film. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0042] Please see Figure 1 This invention provides a method for preparing PI biomimetic nanostructures. The method involves laser scanning of the PI interface and assisted exfoliation with heat-release adhesive tape to obtain independent thin films with nanofunctional surfaces. A 15×15mm film can be prepared within 1 minute. 2 Large-area PI nanostructures are fabricated using laser scanning. The process is simpler and more efficient, and it eliminates the need for biological templates, enabling large-area fabrication. The nanomorphology of the PI film surface prepared using this invention can achieve a highly biomimetic dragonfly wing-like surface morphology. Furthermore, the morphology parameters of the nanostructure can be significantly controlled through process parameters, which is a major advantage for fabricating biomimetic micro / nanostructure surfaces.
[0043] The preparation method mainly includes the following steps:
[0044] Step 1: Spin-coating and curing a PI film on a glass substrate, with the thickness of the PI film controlled between 1 μm and 20 μm.
[0045] Before preparing the PI film, the glass substrate can be pretreated to remove surface contaminants, specifically by wiping the glass substrate with alcohol.
[0046] Step 2: After passing through the glass substrate, the ultraviolet laser is used to scan the PI film, causing nanoscale cavitation to occur at the interface of the laser scanning area to achieve a sub-exfoliated state. At this time, nanofiber connections are generated at the interface between the PI film and the glass substrate.
[0047] By adjusting the laser process parameters, the ultraviolet laser is allowed to pass through the glass and scan the PI film. By controlling the process parameters, nanoscale cavitation occurs at the PI interface in the laser scanning area, causing the interface to reach a sub-exfoliated state. At this point, nanofiber connections are formed between the PI film and the transparent substrate.
[0048] In this embodiment, a nanosecond laser is used. The laser's process parameters mainly include laser pulse energy, pulse frequency, and spot size. The processing parameters include the number of laser scan repetitions and the spot scanning path. The OptoSytem CL7020 XeCl nanosecond laser is preferred, with a center wavelength of 308 nm and a laser energy density of 70 mJ / cm². 2 -120mJ / cm 2 The number of repeated irradiations ranges from 10 to 900.
[0049] Step 3: Apply heat-release tape to the PI film, and use the external force of the heat-release tape to peel the PI film off the glass substrate.
[0050] Step four: Heat the heat-release tape to complete the heat release of the PI film, thereby obtaining the PI biomimetic nanostructure.
[0051] The heat-release tape was heated at 110℃ to complete the heat release process of the PI film, thereby preparing an independent PI film with a nanostructured surface.
[0052] The present invention also provides a PI biomimetic nanostructure, which is prepared by the PI biomimetic nanostructure preparation method described above.
[0053] The present invention also provides an application of the PI biomimetic nanostructure described above in hydrophobic structures.
[0054] The present invention will be further described in detail below with reference to embodiments.
[0055] This embodiment provides a method for preparing PI biomimetic nanostructures, specifically a method for preparing PI-based antireflective surfaces with controllable nanostructures, mainly including the following steps:
[0056] (1) Surface pretreatment: Wipe the glass substrate and PI surface with alcohol to remove surface contaminants.
[0057] (2) Laser etching: An OptoSytem CL7020 XeCl nanosecond laser was used, with a center wavelength of 308 nm and a laser energy density of 70 mJ / cm². 2 -120mJ / cm 2 The irradiation was repeated 10 to 900 times to form a nanostructure array on the PI surface.
[0058] (3) Tape peeling: A heat-release tape is smoothly adhered to the PI film, and the PI film is peeled off from the transparent substrate with the help of the external force of the heat-release tape. The heat-release tape is heated at 110°C to complete the heat release process of the PI film, thereby preparing an independent PI film with a nanostructured surface.
[0059] like Figure 2 As shown, the left side shows the dragonfly wing and its surface nanomorphology, while the right side shows the PI nanostructure surface and its surface morphology prepared using this process. At the same scale, the micromorphology of the two is very similar. There are many randomly distributed columnar nanostructures on the surface of the dragonfly wing. The average height of the nanopillars is about 200 nm, the spacing between the nanopillars is 180 ± 30 nm, and the average diameter of the nanopillar dome is about 80 ± 20 nm. This is very close to the scale of the surface nanostructure prepared by this invention.
[0060] Interface evolution of PI-based antireflective surfaces:
[0061] 1. Experimental characterization of interfacial nanoscale cavitation was conducted by observing the raised areas on the PI film surface and performing microscopic observations of the interface after peeling. When the PI was continuously irradiated by a laser, the laser and PI continuously reacted to generate gas, leading to changes in the interfacial state. The interface exhibited three typical states under continuous laser irradiation: unpeeled interface, semi-peeled interface, and fully peeled interface. Figure 3a and Figure 3b As shown.
[0062] 2. When the number of laser irradiations reaches a certain amount, the interface state will be as follows: Figure 4 As shown in b, PI decomposes under laser irradiation, generating a large amount of gas. At the instant the laser irradiates the PI, the temperature of the PI interface exceeds the melting point of PI. Therefore, the generated gas grows inside the molten PI, squeezing outwards to form large elliptical bubbles. At this point, the interfacial connection between PI and the quartz substrate is only the PI fibers existing between the bubbles. Therefore, the interfacial adhesion decreases significantly. Under these interfacial conditions, applying external force to peel the PI film results in the interface breaking at the center of the nanofibers, i.e., interface 2. Nanopillar structures are also observed on both the peeled quartz substrate and the PI film. This state of interface 2, where separation is imminent but the nanofiber structures remain interconnected, is called the sub-peeling state. Figure 4 The right side of d and Figure 4 Nanostructure morphology was observed in the left region of region e, and its planar height was between that of the smooth regions on both sides. As the number of laser irradiations continued to increase, such as... Figure 4 As shown in Figure c, the laser acts on the PI to generate more gas. A sufficient amount of gas will further fuse and completely separate the interface. The nanopillars gradually melt and collapse at high temperature to form a plane. The interfacial nanofiber connections completely disappear, and the interface cavitation is complete. At this point, the interfacial adhesion is already very weak. Figure 4 The presence of nanopillar ablation marks on the right side of 'e' in the image also proves this point; at this point, the film peeling is due to the fracture of interface 3.
[0063] 3. Various measurement methods were used to characterize the state parameters (such as surface elevation height, transmittance, interfacial adhesion, and morphology of peeled PI surface) of the laser-induced interfacial nanoscale cavitation process, revealing the evolution law of the interfacial state under continuous laser irradiation: from an unpeeled state, the interface is tightly connected, then to a sub-peeled state, the interface becomes connected by nanofibers, and finally to a completely peeled state, the interfacial connection is broken or disappears. Through laser energy density and scanning method process parameters, it was found that the rate of interfacial cavitation evolution can be controlled by these parameters, obtaining a complete process window for laser-induced control of interfacial nanoscale cavitation. The results are as follows: Figure 5 As shown.
[0064] 4. Experimental characterization of interfacial nanoscale cavitation was performed by measuring interfacial adhesion forces.
[0065] During adhesion testing, the area covered by each test should be the same, i.e., the coverage area of a 4mm disc, to ensure the comparability of experimental data. Figure 6 This shows the adhesion force under multiple repeated test results. After APN=20 times, the interfacial adhesion force shows a clear downward trend as APN increases. This indicates that the interfacial reaction generated by laser irradiation of the interfacial area directly leads to a gradual weakening of the adhesion force between the interfaces. Moreover, the interfacial adhesion force can be precisely controlled by controlling the number of irradiations. In the figure, the interfacial adhesion force decreases from nearly 50N to about 2N as the number of irradiations increases. In the experiment, when the adhesion force drops to about 20N, the PI film and the substrate enter a state where they are very easy to peel off. When the adhesion force drops below 5N, the PI film and the substrate have been completely peeled off. The precise control of the adhesion force over a large range provides a foundation for realizing non-destructive peeling of devices.
[0066] 5. Experimental characterization of interfacial nanoscale cavitation was performed by measuring interfacial transmittance.
[0067] During the continuous laser irradiation of the PI film, transmittance measurements were performed on the sample every 5 irradiations. Transmittance at wavelengths of 500nm, 600nm, 700nm, and 800nm was extracted, and the experimental results are as follows: Figure 7 As shown, it can be observed that under the first 20 irradiations, the transmittance of all wavelengths gradually decreases. As the number of irradiations is further increased (30-60 times), the transmittance of all wavelengths rebounds and reaches a peak. When the number of irradiations is high enough (>60 times), the transmittance of all wavelengths decreases with the increase of the number of irradiations.
[0068] Nanostructures are controlled by the number of laser irradiations: 105 mJ / cm² is selected. 2 By using a fixed laser energy density, the effect of the number of laser irradiations on the microstructure of the PI surface was studied. Within the process range suitable for fabricating nanostructures, samples were prepared by adjusting the APN (Active Laser Point Density) to 20, 40, and 60 irradiations. The surface of the peeled PI film was then observed under an electron microscope. Figure 8 In the image, 'a' represents a SEM planar image taken when the sample is placed horizontally. Figure 8In the image, b represents the side view (rotated 52°) under the corresponding APN. To reduce the occlusion of the nanopillars, the lower half of the ablated black area in the image was removed to a depth of ~300 nm using FIB. From the front view of the nanostructure, it can be observed that as the APN increases from 20 to 60, the overall density distribution of the nanopillars clearly changes from dense to sparse, and the proportion of black area in the entire image increases, but the size and morphology of individual nanopillars do not change significantly. The phenomenon of the nanopillars changing from dense to sparse is also clearly observed from the side view. Simultaneously, it can be found that when the APN increases from 20 to 40, the height of the nanopillars increases significantly. Statistical results are as follows... Figure 9 As shown.
[0069] Controlling nanostructures through laser energy density: Laser energy density affects the process window for interfacial cavitation. Appropriately reducing the laser energy density can increase the APN range for controlling the interfacial cavitation effect. Increasing the laser energy density actually accelerates the evolution rate of interfacial cavitation without affecting the trend of the APN increasing the distribution of nanopillars from dense to sparse. Figure 10 This image shows the nanomorphology of the PI film surface near the exfoliation endpoint of the APN at four different energy densities. In the side view, the nanopillar morphology is clearly displayed, revealing a root-like structure at the base of each nanopillar, which eventually converges into a single nanopillar growing upwards. The height of a single nanopillar is measured as the distance from the substrate plane to the top of the nanopillar. The height of the nanopillars at the same energy density is not a constant value; the distribution of nanopillars varies in height. A significant increase in nanopillar height is observed as the laser energy density decreases. Statistical results are shown below. Figure 11 As shown.
[0070] Controlling Nanostructures Through Laser Scanning Direction: Investigating the Influence of Unidirectional and Cross-Scanning Methods on Nanostructure Morphology at 90 mJ / cm 2 At a fixed energy density, the scanning directions were set as unidirectional scanning (vertically downward) and vertical cross scanning (horizontal and vertical superposition scanning directions), and the PI nanosurface was observed using electron microscopy under both scanning methods. Figure 12 a in Figure 12 In the image, b represents the image taken when the sample is horizontal. Figure 12 a1 in Figure 12 a2 in Figure 12 b1 in Figure 12 In the image, b2 is a side view taken after the sample stage is rotated 52°. The X and Y directions represent the shooting directions of the corresponding SEM images. For unidirectional scanning, when the laser scanning direction is vertically downward, Figure 12In the image 'a', numerous lateral nanopillar clusters are observed. When viewed from the X-axis, the nanopillars appear as sharp, upright columns, while in the Y-axis, the nanostructures resemble continuous mountain peaks. This difference in appearance between the two directions is reminiscent of the ancient Chinese poem "viewed horizontally, a ridge; viewed from the side, a peak," suggesting that the morphology of the nanostructure is similar to a thin nanosheet, exhibiting significant anisotropy. For cross-scanning, where the laser beam is superimposed along the horizontal and vertical directions, [further details can be observed]. Figure 12 In the nanopillars in section b, the nanopillars are more independent, with almost no clusters along a fixed direction. Both the X and Y sides show sharp, upright columnar shapes, indicating that the overall morphology is indeed composed of individual nanopillars, exhibiting isotropic properties. This structure is believed to be related to laser-induced surface periodicity. Because laser light has significant polarization characteristics, it may lead to uneven energy deposition. By using bidirectional scanning, the laser energy can be effectively contributed to the material surface, forming a uniformly distributed nanostructure.
[0071] The application performance of the antireflection structure was verified.
[0072] The resulting structure exhibits antireflection and anti-reflection properties: In this embodiment, a smooth PI film (12 μm) was used as a control group. Compared to the smooth PI film, the PI film with nanostructures showed at least a 4% increase in transmittance and a 4% decrease in reflection. Furthermore, nanostructured PI films with higher APN tend to have higher transmittance and lower reflection. The antireflection and antireflection effect was best at APN=50, where the overall transmittance of the nanostructured PI film increased by approximately 7% and the overall reflectance decreased by approximately 7%. Moreover, due to the absorption of ultraviolet light by the PI film, the surface reflectance reached only 1.5% at around 400 nm. The antireflection effect of the nanostructured PI surface prepared in this invention has reached a medium-to-high level, as shown in the results. Figure 13 .
[0073] The resulting structure surface exhibits superhydrophobicity: the left frame shows a PI film with a nanostructured surface, while the right frame shows a PI film with a smooth surface. 1 μL of deionized water was added to both regions. The droplet on the left appeared spherical, while the droplet on the right spread out on the surface. Further quantitative analysis of the hydrophobic effect of the PI nanostructured surface using a contact angle meter revealed that the static contact angle of the PI nanostructured surface reached 133°, while the static contact angle of the smooth control PI surface was 85.2°. This demonstrates that the nanostructure morphology of the surface can alter the wettability of the material itself. The nanostructure morphology of the PI surface increased the contact angle of the PI surface by nearly 48°, changing the PI surface from hydrophilic to hydrophobic. This shows that surface nanostructures can be used to significantly control the hydrophilicity and hydrophobicity of a surface. Because the nanostructure prepared in this invention is particularly similar to the nanostructure on the surface of dragonfly wings, its hydrophobicity was also measured and compared with that of the dragonfly wing surface. The measurement results showed that the static contact angle of the dragonfly wing was 133.7°, which is at the same level as the contact angle achievable by the PI nanostructure surface in this invention. Figure 14 As shown.
[0074] The PI nanofilms prepared using this process exhibit good antireflection properties in the 600nm–800nm wavelength range, but poor transmittance in the blue-violet light range of approximately 400nm–550nm. This is due to the strong absorption of blue-violet light by the PI material itself. To address this issue, the existing process is optimized (e.g., ...). Figure 15 As shown in the figure, by reducing the thickness of the PI film spin-coated on the glass substrate to the submicron level, and continuing to prepare a transparent PI layer on top of the ultrathin PI, a transparent PI film with a nano-PI coating on the surface can be obtained by laser scanning cavitation exfoliation. The results are as follows. Figure 15 As shown, the presence of PI nanofilms exhibits significant antireflection and antireflection effects, maintaining stable antireflection properties even at large angles. The performance of transparent PI coated with PI nanofilms is comparable to that of dragonfly wings in terms of light-trapping properties, as demonstrated by the results. Figure 16 As shown. It is important to note that during laser scanning, a pre-stripping area needs to be irradiated at the edge of the PI film, such as... Figure 17 As shown.
[0075] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing PI biomimetic nanostructures, characterized in that, The method includes the following steps: (1) A PI film is prepared on a substrate, and a pre-peeling area is irradiated at the edge of the PI film. An ultraviolet laser with a center wavelength of 308 nm is used to scan the PI film after passing through the substrate, so that the interface of the laser scanning area undergoes nanoscale cavitation to achieve a sub-peeling state. At this time, nanofiber connections are generated at the interface between the PI film and the glass substrate. The scanning adopts a vertical cross scanning method, and the scanning direction is a combination of horizontal and vertical. (2) Apply heat-release tape to the PI film and use the external force of the heat-release tape to peel the PI film off the glass substrate; (3) The heat release tape is heated at 110°C to complete the heat release of the PI film, thereby obtaining a PI biomimetic nanostructure on the surface of the submicron thick PI film. Among these methods, the PI biomimetic nanostructure can be controlled by the laser scanning direction, and isotropic independent nanopillar structures can be obtained through vertical cross-scanning; the laser energy density is 70 mJ / cm². 2 -120mJ / cm 2 The number of repeated irradiations ranges from 10 to 900; the overall transmittance of the PI film is 7% higher than that of the smooth film.
2. The method for preparing the PI biomimetic nanostructure as described in claim 1, characterized in that: The thickness of the PI film is 1µm to 20µm.
3. The method for preparing PI biomimetic nanostructures as described in claim 1, characterized in that: The number of repeated irradiations is 50.
4. The method for preparing the PI biomimetic nanostructure according to any one of claims 1-3, characterized in that: The height of nanopillars on the surface of PI biomimetic nanostructures can be increased by increasing laser energy density and the number of irradiations.
5. The method for preparing PI biomimetic nanostructures as described in claim 4, characterized in that: The density of the nanopillars can be adjusted by regulating the fixed laser energy density and the number of irradiations.
6. A PI biomimetic nanostructure, characterized in that: The PI biomimetic nanostructure is prepared using the preparation method of the PI biomimetic nanostructure according to any one of claims 1-5.
7. The application of the PI biomimetic nanostructure as described in claim 6 in a hydrophobic structure.